Crude microcystins extracted from Microcystis aeruginosa exert anti-obesity effects by downregulating angiogenesis and adipogenesis related signaling molecules in HUVEC and 3 T3-L1 cells - Muhammad Imran Khan; Jin Hyuk Shin; Jong Deog Kim (BMC, 2019)
Abstract Background Obesity is a risk factor for many diseases including diabetes, cancer, arthritis, and cardiovascular diseases. Angiogenesis nourishes adipose tissues and contributes to obesity; it can be prevented by suppressing the expression of associated signaling molecules. Natural products have garnered attention owing to their safety and efficacy in treating several diseases, including obesity. Methods Crude Microcystins were extracted from the blooming Microcystis aeruginosa under stress conditions, by ultrasonication following by solvent extraction. The microcystin extract was evaluated for its potential of inhibiting angiogenesis and adipogenesis. The antiangiogenic activity of the microcystins extract was investigated using human umbilical vein endothelial cells (HUVECs), and its anti-obesity activity was determined in vitro by quantification of the accumulated lipids in mouse 3 T3-L1 cells via Oil Red O staining method. Results The microcystin extract suppressed HUVECs proliferation and tubes formation in Matrigel in a dose-dependent manner. RT-PCR analysis revealed the downregulation of the mRNA expression of angiogenesis-related signaling molecules, such as PI3K, β-catenin, vascular endothelial growth factor receptor-2 (VEGFR-2), vascular endothelial-cadherin, Akt1, and NF-κB. Additionally, it inhibited the differentiation of premature 3 T3 cells and lipid accumulation in a dose-dependent manner. It suppressed adipogenesis and lipogenesis by reducing the expression level of peroxisome proliferator-activated receptor γ, CCAAT/enhancer binding protein α, and sterol regulatory element-binding protein. Conclusions Crude microcystin exerts anti-angiogenic and anti-obesity effects due to the inhibitory effects on the genes expression of associated signaling molecules and transcriptional factors.